Cesarean delivery in the obese parturient: anesthetic considerations. (March 2011) - Loubert, Christian; Fernando, Roshan
Obesity is a worldwide health problem and its prevalence is reaching epidemic proportions. As obesity does not spare women of childbearing age, obstetric anesthesiologists will increasingly be exposed to the challenges of anesthesia in this population. The purpose of this article is to give the reader a thorough understanding of the anesthetic implications of obesity relating to cesarean deliveries. Obesity is associated with hypertension, diabetes, obstructive sleep apnea and other comorbidities. It increases the risk of cesarean delivery, postpartum wound infections and deep venous thromboembolism. Obese parturients are prone to anesthetic complications such as aspiration of gastric contents, difficult monitoring, positioning, airway management and challenging neuraxial techniques. A thorough precesarean delivery preparation should include an evaluation by an anesthesiologist for women with a BMI over 40 kg/m 2 and institution of an antacid prophylaxis protocol, thromboprophylaxis and antibiotic prophylaxis. Regional anesthesia should ideally be used in all obese parturients unless contraindicated. The goals of postpartum care include efficacious analgesia, physiotherapy and early mobilization. Monitoring and vigilance in an intensive care unit or step-down units should be considered for morbidly obese women.